2007
DOI: 10.1001/archotol.133.12.1263
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Altered Toll-like Receptor 4 Signaling on Cancer Cachexia

Abstract: To determine whether mice unable to mount an intact inflammatory response because of a Toll-like receptor (TLR) pathway defect will develop less severe cancer cachexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Genetic phenotypes, especially associated with immune signaling pathways, seem to be involved in the magnitude of the cachexia that develops. Inducing head and neck cancer in a preclinical model using cogenic murine strains with a double mutation in the toll‐like receptor 4 signaling pathway identified that the mouse strain with an intact inflammatory signaling pathway had more cachexia with smaller tumors than the strain with the defect in the toll‐like receptor 4 pathway . A handful of candidate genes to explain genetic polymorphisms in cancer cachexia have been reviewed recently and necessitate further study in patients and trials.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic phenotypes, especially associated with immune signaling pathways, seem to be involved in the magnitude of the cachexia that develops. Inducing head and neck cancer in a preclinical model using cogenic murine strains with a double mutation in the toll‐like receptor 4 signaling pathway identified that the mouse strain with an intact inflammatory signaling pathway had more cachexia with smaller tumors than the strain with the defect in the toll‐like receptor 4 pathway . A handful of candidate genes to explain genetic polymorphisms in cancer cachexia have been reviewed recently and necessitate further study in patients and trials.…”
Section: Methodsmentioning
confidence: 99%
“…80 Both wild-type and TLR-non-functional mice were inoculated with squamous carcinoma cells and compared. The wild-type mice weighed less on average than the TLR-non-functional mice.…”
Section: Role Of Inflammatory Molecules In Cancer-related Symptomsmentioning
confidence: 99%
“…These results indicated that the impaired ability to secrete IL-1 β may protect TLR-deficient mice from developing severe cancer cachexia. 80 One study of gastric cancer patients from China examined the predictive value of IL-1 β gene polymorphism for cachexia. Of the four alleles (IL-1 β -31 T/C, −511 C/T, +3954 C/T, IL-1RN), IL-1 β + 3954 C/T was found to be a major risk for cachexia in gastric cancer patients.…”
Section: Role Of Inflammatory Molecules In Cancer-related Symptomsmentioning
confidence: 99%
“…Previously Cannon et al . observed that mice with nonfunctional TLR4 due to a TLR4 double mutation (TLR4 d/d ) were resistant to cachexia induced by squamous cell carcinoma SCCF VII cells, and suggested that TLR4 mediated muscle wasting by increasing circulating IL-1β 22 . However, the detailed mechanism through which TLR4 mediates cancer-induced muscle wasting remains unknown.…”
Section: Introductionmentioning
confidence: 99%